Escrita alfabética, suporte, comunicação e linguagens possíveis - Lopes, Andrea Olympio de Mello Machado (2007)
This research is about the alphabetic written sign and its transformations in the variety of media. Also about its origin in new supports, the decurrent significations, the language produced in them and by them, its common traces and new ways shown. So, some aspects must be analyzed: the hypotheses that the alphabetic written sign is not facing a process of extinction but only a process of transformation, manifestating itself in alternative medias and, therefore, starts making use of new supports and medias that, originally, did not preview its use. This fact brings some transformations in its original language and the appearing of dialects. The central purpose of this work is to identify and understand the current transformations of the alphabetic written sign through its behavior in the cultural environment and its manifestation in some different medias and supports, we mean, the characteristics of the verbal sign when, suffering the interference of other communicative characteristics, it abandons the double dimensional and contiguous structure of its spatiality and starts interacting with spatiality that confer them movement, a triple dimensional structure and other characteristics of cultural, cognitive and sign mediation. The corpus to be analyzed is composed by different supports that make use of the verbal sign that was collected through field research. To the analyses, the theoretical field adopted will be the Semiotics of Culture, approaching the concepts Semiosphere, Texts from Culture, Heteroglossia, Visual Culture, Modelization Systems, Discreet and Not-discreet Language. So, we intend to identify the role that the verbal assumes in the Occidental Culture, its current language and the new ways shown by and for them. The fundamental bibliography of this research is composed by the following theoretical fields: Semiotics of Culture, Theory of Communications, means of communication, Linguistics, Culture of Medias, Theories of Writing